Isokinetic peak torque ratios and shoulder injury history in adolescent female volleyball athletes - Stickley, C. D.; Hetzler, R. K.; Freemyer, B. G.; Kimura, I. F. (Journal of Athletic Training, 2008)
Few researchers have examined shoulder strength in adolescent volleyball athletes despite increasing levels of participation in this age group.